Fish in the lakes, wild rice, and game in abundance : testimony on behalf of Mille Lacs Ojibwe hunting and fishing rights - McClurken, James M.; Cleland, Charles E., 1936- (Book collections on Project MUSE., 2000)
"On 13 August 1990 members of the Mille Lacs Band of Ojibwe filed a lawsuit against the State of Minnesota for interfering with the hunting, fishing, and gathering rights that had been guaranteed to them in an 1837 treaty with the United States. In order to interpret the treaty the courts had to consider historical circumstances, the intentions of the parties, and the treaty's implementation. The Mille Lacs Band faced a mammoth challenge.